Involvement of integrin αvβ3 in thyroid hormone-induced dendritogenesis - Ariyani, Winda; Miyazaki, Wataru; Amano, Izuki; Koibuchi, Noriyuki (Frontiers in Endocrinology, 2022)
Activation and/or modulation of the membrane-associated receptors plays a critical role in brain development. Thyroid hormone (TH) acts on both nuclear receptors (thyroid hormone receptor, TR) and membrane-associated receptors, particularly integrin αvβ3 in neurons and glia. Integrin αvβ3-mediated signal transduction mediates various cellular events during development including morphogenesis, migration, synaptogenesis, and intracellular metabolism. However, the involvement of integrin αvβ3-mediated TH action during brain development remains poorly understood. Thus, we examined the integrin αvβ3-mediated effects of TH (T3, T4, and rT3) in the neurons and astrocytes using primary cerebellar culture, astrocyte-enriched culture, Neuro-2A clonal cells, and co-culture of neurons and astrocytes. We found that TH augments dendrite arborization of cerebellar Purkinje cells. This augmentation was suppressed by knockdown of integrin αvβ3, as well as TRα and TRβ. A selective integrin αvβ3 antagonist, LM609, was also found to suppress TH-induced arborization. However, whether this effect was a direct action of TH on Purkinje cells or due to indirect actions of other cells subset such as astrocytes was not clarified. To further study neuron-specific molecular mechanisms, we used Neuro-2A clonal cells and found TH also induces neurite growth. TH-induced neurite growth was reduced by co-exposure with LM609 or knockdown of TRα, but not TRβ. Moreover, co-culture of Neuro-2A and astrocytes also increased TH-induced neurite growth, indicating astrocytes may be involved in neuritogenesis. TH increased the localization of synapsin-1 and F-actin in filopodia tips. TH exposure also increased phosphorylation of FAK, Akt, and ERK1/2. Phosphorylation was suppressed by co-exposure with LM609 and TRα knockdown. These results indicate that TRs and integrin αvβ3 play essential roles in TH-induced dendritogenesis and neuritogenesis. Furthermore, astrocytes-neuron communication via TR-dependent and TR-independent signaling through membrane receptors and F-actin are required for TH-induced neuritogenesis.